2014
DOI: 10.1097/adm.0000000000000064
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cannabis Withdrawal and Its Influence on Adolescents' Treatment Response and Outcomes

Abstract: Background Withdrawal, a diagnostic indicator of cannabis use disorder, is often minimized or ignored as a consequence of cannabis use, particularly among adolescents. This study aims to characterize cannabis withdrawal among adolescents in outpatient treatment for substance use disorder and evaluate the clinical significance of withdrawal as a predictor of substance-related outcomes. Methods Adolescent outpatients (N=127) reporting cannabis as their drug of choice (n=90) were stratified by presence of withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 34 publications
(59 reference statements)
0
38
1
1
Order By: Relevance
“…Additionally, many prior studies on cannabis withdrawal investigated treatment-seeking cannabis users with more frequent, heavier and earlier initiation of use than the average participant enrolled in the current trial. It is therefore possible that patterns of withdrawal by psychiatric history may differ for more severe patient populations 23, 5051 . Another noteworthy limitation is that, although the time since last cannabis use was within one week of the baseline visit, it was not standardized beyond that parameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, many prior studies on cannabis withdrawal investigated treatment-seeking cannabis users with more frequent, heavier and earlier initiation of use than the average participant enrolled in the current trial. It is therefore possible that patterns of withdrawal by psychiatric history may differ for more severe patient populations 23, 5051 . Another noteworthy limitation is that, although the time since last cannabis use was within one week of the baseline visit, it was not standardized beyond that parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis withdrawal has been identified as a key criterion of cannabis use disorder 21,22 , impacting between 35% to 75% of adolescents and young adults with a use disorder attempting to reduce or discontinue use 23 . According to the DSM-V, the cannabis withdrawal syndrome involves the manifestation of three or more of the following six symptoms: irritability or anger; nervousness or anxiety; sleep difficulty (i.e., insomnia, disturbing dreams); decreased appetite or weight loss; restlessness; depressed mood; and at least one physical symptom causing discomfort (i.e., abdominal pain, shakiness/tremors, sweating, fever, chills, headache) 2426 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cannabis withdrawal was associated with difficulty achieving abstinence in two cross-sectional, retrospective-recall studies (Budney, Vandrey, Hughes, Thostenson, & Bursac, 2008; Cornelius et al, 2008), only two studies have prospectively investigated whether cannabis withdrawal predicts posttreatment abstinence (Arendt et al, 2007; Greene & Kelly, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Greene and Kelly (2014) reported that adolescents endorsing one or more withdrawal symptom had equivalent posttreatment outcomes compared with those not experiencing withdrawal (Greene & Kelly, 2014). However, the presence of withdrawal interacted with problem recognition, with those reporting withdrawal and ability to acknowledge problems having better posttreatment outcomes.…”
Section: Introductionmentioning
confidence: 99%